Assessment of El Niño impacts and grain trade policy responses in East and Southern Africa - Mamun, Abdullah; Chapoto, Antony; Chisanga, Brian; D’Alessandro, Stephen; Koo, Jawoo; Martin, Will; Samboko, Paul (International Food Policy Research Institute, 2018)
This study analyzes recent household data on Malawi, Tanzania, and Zambia to assess the impact of the most recent El Niño in East and Southern Africa and the trade policy responses to it. Its findings suggest that although these policies helped some low-income consumers of maize, they resulted in notable market volatility—and they exacerbated the adverse impacts of drought-affected yields for many low-income farm households. Indeed, in Zambia the downside impacts of the export ban on the poor appear to have greatly exceeded the impacts of El Niño itself and amplified food security concerns in importing countries, such as Malawi. Given the detrimental effects of these policies, a strong case exists for alternative policies that help reduce market price volatility and safeguard poor households’ welfare and access to food.